Reading Myself Elsewhere. A Few Notes on Reading Otherwise (Comparatismi, 2018)
This essay investigates the emotional attachments we bring to a book: we will describe the identification processes that reading may involve, and how these processes affect the reader’s experience and identity. When it is authentic, the act of reading cannot be considered as a moment of mirroring, but it includes a more profound identification experience to the extent that reading becomes a sort of event, a gesture that at times may alter the reader’s perception of her identity since, through it, she can access the buried spaces of the unconscious. If it is true that every work demands an interpretation, at the same timethe fruition of literary texts by readers is inextricably linked to their desire for personal knowledge. This is why reading is neither a cognitive nor a psychobiological experience, insofar as it involves a more complex and personal interpretative and intersubjective activity: reader and text become a sort of innovative enterprise through which connections are not only unmasked, but above all continuously created. For the purposes of the discussion and to illuminate better the point I want to make, I will implicate myself and my own personal experience as reader of Sylvia Plath.